Strengthening Practices Education In The Framework of Islam and Gayo Community Culture - Ramsah Ali; Suwarno Suwarno; Kharisul Wathoni; Masruchan Masruchan; Mashur Mashur (Syntax Corporation Indonesia, 2021)
Moral education is a part that cannot be separated from religious education, because what is good according to morals is also good according to religion, and bad according to religious teachings is also bad for morals. Morals in Islamic life are not just a model or a lifestyle that a Muslim may abandon at any time. Morals are not clothes that can be worn and then removed whenever desired. However, morality is a functionalization of religion, meaning that diversity will be meaningless if it is not proven by morality. Strengthening moral education in today's modern era is very important to fortify generations from the negative influence of the development of science and technology, especially information technology which can all be accessed through smartphones. This study aims to formulate moral education to fortify generations from moral decline. This research is a library research, to build a concept or theory that becomes the basis of study in research. The data used in this study is qualitative data in the form of concepts, theories, and formulations that are relevant to the research made. The data analysis used is content analysis and descriptive analysis to analyze the culture of the Gayo community related to moral education. The results of the research related to strengthening moral education in the culture of the Gayo community, among others, through strengthening the value system of Gayo culture in society and through strengthening the application of Sumang and Kemali concepts in Gayo culture.